Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1606/1044-3894.1051
|View full text |Cite
|
Sign up to set email alerts
|

A Template for Family-Centered Interagency Collaboration

Abstract: In this paper, it is asserted that successful interagency collaborations require commitment to a shared value base as the core dimension of the joint efforts. A rationale framework that places family-centered principles at the core is provided, and how these principles translate into specific behaviors, attitudes, and policies on all levels within and between organizations is outlined. This template can provide guidance to local and state policy makers involved in reforming systems of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…To date families' experiences of negotiating with systems for the care of their children has been largely unstudied and misunderstood (Christian & Gilvarry, 1999;Rose, 2002;Ungar, 2003;Walter & Petr, 2000;Whittaker, 2000). Those that have taken on this task have found that preliminary findings leave many questions unanswered.…”
Section: Resilience As Structurementioning
confidence: 99%
See 1 more Smart Citation
“…To date families' experiences of negotiating with systems for the care of their children has been largely unstudied and misunderstood (Christian & Gilvarry, 1999;Rose, 2002;Ungar, 2003;Walter & Petr, 2000;Whittaker, 2000). Those that have taken on this task have found that preliminary findings leave many questions unanswered.…”
Section: Resilience As Structurementioning
confidence: 99%
“…Families and their communities and the systems that serve them must invert their relationships, such that families and communities are the drivers of how systems are organized and services delivered (Christian & Gilvarry;1999;Ungar, 2004;Walter & Petr, 2000). As an exemplar of what can be accomplished, Vander Stoep and her colleagues (Vander Stoep, Green, Jones, & Huffine, 2001) report on their evaluation of a family empowerment program called the King County Blended Funding Project.…”
Section: In Practice and Policymentioning
confidence: 99%
“…Literature has described it as ''common mission'' (Alexander et al 1998;Roussos and Fawcett 2000), ''common ground'' (Wondolleck and Yaffee 2000), ''common purpose'' (Tett et al 2003), ''common aims'' (Huxham 2003), ''common objectives'' (Padilla and Daigle 1998), ''shared vision'' (Manring and Pearsall 2004;Walter and Petr 2000;Wondolleck and Yaffee 2000), ''shared ideology'', ''clear goals'' (Glasbergen and Driessen 2005;Roberston and Lawes 2005), ''clear and strategic direction'' (Margerum 2001), or the ''alignment of core values'' (Heikkila and Gerlak 2005). Shared understanding can also imply agreement on a definition of the problem (North 2000;Bentrup 2001;Pahl-Wostl and Hare 2004) or, it might mean agreement on the relevant knowledge necessary for addressing a problem (Ansell and Allison 2008).…”
Section: Shared Leadership Identity and Understandingmentioning
confidence: 99%
“…In addition, collaboration allows agencies to better coordinate services, reduce deficiencies (i.e., children "falling through the cracks"), and address a lack of qualified or trained personnel (Huxham, Vangen, & Eden, 2000;Johnson, Tam, Zorn, LaMontagne, & Johnson, 2003;Pfeiffer & Cundari, 2000;Prince & Austin, 2005;Walter & Petr, 2000). Furthermore, there are sound financial reasons for collaboration, most notably the efficiencies produced by avoiding duplication of services and the ability to spread the cost and risk of a large initiative across several agencies (Huxham et al, 2000;Johnson et al, 2003;Mattessich & Monsey, 1992;Walter & Petr, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%